(untitled) (Medico Legal Update, 2021)
Amebiasis is an important cause of diarrheal disease worldwide and has been associated with childhood malnutrition. E.histolytica diagnosed usually by microscope, which consider as traditional diagnosis and are neither sensitive nor specific detection of Entamoeba histolytica(1). Real-time PCR assay developed for sensitive and specific detection of the intestinal Protozoan parasites Entamoeba histolytica directly from human feces(2). The RT-PCR assay was able to detect as little as 0.1 parasite per g of feces(3). The current study based on Phosphoglycerate kinase gene (PGK) is a major enzyme used in glycolysis, in the first ATPgenerating step of the glycolytic pathway so the PGK is an enzyme that catalyzes the reversible transfer of a phosphate group from 1,3-bisphosphoglycerate (1,3-BPG) to ADP producing 3-phosphoglycerate (3-PG) and ATP(4). In our study, depend on PGK as target for Real time PCR assay for detection the trophozoite stage of E.histolytica in stool samples of infected persons. In the current study, a total of 300 human fecal samples were collected from children (less than one year-15 year) that suspected to infection with amoebiasis which admitted to hospitals and primary care centers in the city center, Al-Hindiya district and Nahiat Al -Hurr (100 samples from each region) during the period from February 2019 to January 2020. Fecal samples processed by direct wet smear and formalin ethyl acetate concentration method followed by iodine staining and was microscopically examined for E.histolytica. Microscopically positive samples were then subject to Real-time PCR. This is the first study in Iraq using the Phosphoglyceratekinase gene as target for molecular techniques to determine the presence of E. histolytica trophozoites.in stool samples.